Alternative resolution of public law disputes in administrative proceedings of European Union member states - Yaroshenko, Oleg M.; Pyzhov Oleksandr М.; Arsentieva, Olena S.; Harashchuk Volodymyr М.; Inshyn, Mykola I. (P.A. Persona e Amministrazione, 2022)
The unloading and effectiveness of administrative courts largely depends on effective mechanisms for legal protection of the rights and legitimate interests of individuals and legal entities, one of which is the alternative resolution of public law disputes. The article analyzes the positive experience of the European Union, which formed a regulatory array of acts on alternative dispute resolution. The purpose of the study is to implement the theoretical and legal characteristics of the procedural features of the institute of alternative resolution of public law disputes in the administrative proceedings of the European Union, as well as to provide proposals for prospects for its improvement. The methodological basis of the study is a set of general scientific, philosophical, special methods of scientific knowledge, the use of which allowed to ensure the achievement of the stated goals and objectives of the study and comprehensive coverage of the research problem. The urgency of the work lies in the scientific and practical need to study the little-studied topic of procedural features of alternative resolution of public disputes in the administrative proceedings of Ukraine.